Dairy Sector: Opportunities and Sustainability Challenges - Bhat, Rajeev (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Achieving success along the entire production and supply chain of a dairy sector depends explicitly on adopting a sustainable 'state of the art' approach. In this regard, understanding key sustainability indicators and challenges with a holistic approach is vital. Appropriate design, application of novel technologies, implementation of life cycle analysis, upgradation and optimization of the entire production line are some of the key factors to be measured. In addition, it is vital that due consideration is given to demands of the producers, consumers, and dependent industries. Nevertheless, concern for the environment, social security and economy of the region should not be ignored. Precise planning ('on-farm' and 'off-farm') assumes importance especially when circular economy strategies needs to be considered. With these as background, this book is focused towards identifying present opportunities and overcoming future sustainability challenges in the global dairy sector.